2008
DOI: 10.1002/jsfa.3302
|View full text |Cite
|
Sign up to set email alerts
|

Potato glycoalkaloids: formation and strategies for mitigation

Abstract: With the increasing production and consumption of potato and its products, glycoalkaloid (GA) formation and toxicity are likely to become an important focus for food safety researchers and public health agencies. Not only the presence of GA, particularly in the form of α-solanine and α-chaconine, but also the changes occurring as a result of various post-harvest handling practices and storage, are critical issues influencing the quality of stored potatoes. Studies on various factors (pre-harvest, during harves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 150 publications
2
51
0
3
Order By: Relevance
“…to 24.45 mg 100 g −1 f.w. nema et al [23] reported that Tga content in frozen peels of different edible varieties ranged from 6.5 to 12.1 mg 100 g −1 f.w. Many authors, Friedman and Dao [6], Wünsch and Munzert [39], Friedman [5], and Friedman and levin [7], reported that most Tga in the tuber are accumulated in the peel, especially in the area of eyes, whereas the distribution of Tga in a tuber differs among varieties.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…to 24.45 mg 100 g −1 f.w. nema et al [23] reported that Tga content in frozen peels of different edible varieties ranged from 6.5 to 12.1 mg 100 g −1 f.w. Many authors, Friedman and Dao [6], Wünsch and Munzert [39], Friedman [5], and Friedman and levin [7], reported that most Tga in the tuber are accumulated in the peel, especially in the area of eyes, whereas the distribution of Tga in a tuber differs among varieties.…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of α-solanine to α-chaconine varies between varieties, although α-chaconine usually occurs in distinctly higher concentration than α-solanine [6,8,16,23,30,37]. The scientific literature most frequently has provided data on the ratio of α-solanine to α-chaconine in lightfleshed varieties.…”
Section: Tga Content After Peelingmentioning
confidence: 99%
See 3 more Smart Citations